Monitoring of cash execution of the state budget during the implementation of national projects and the choice of economic development directions - I. I. Chebyshev (Вестник университета)
The article emphasizes the importance of financial monitoring as an element of control over the implementation of national projects and, in particular, cash execution. The paper carries out the analysis of monitoring of the federal budget execution in terms of budget allocations for the implementation of national projects for the first half of 2019. The study reveals trends of cash execution. The author identifies a lag in the rate of execution of expenditures for the implementation of national projects from expenditures that are not related to national projects. The article studies the structure of federal budget expenditures and identifies the specifics that affect the lag in the pace of implementation of public expenditures. The paper gives the list of specific factors that have an impact on the backlog in the implementation of the federal budget. The author considers the areas for development and the necessary further actions to eliminate the identified problems.